Bacterial surface roughness regulates nanoparticle scavenging in seawater. Issue 4 (27th January 2023) - Yamada, Yosuke; Patel, Nirav; Fukuda, Hideki; Nagata, Toshi; Mitarai, Satoshi; Azam, Farooq
Abstract: Organic nanoparticles are abundant in marine environments and constitute important nutrient sources for bacteria. Bacteria have evolved cell surfaces over 3.8 billion years to efficiently utilize food particles, and they contribute to material cycling in the world's oceans. Nanoscale roughness of bacterial cell surfaces reflects outer membrane structures and extracellular polymers that potentially affect cell–particle interactions. However, the variability of surface roughness of marine bacteria has been little studied and its involvement in nanoparticle attachment to bacteria is essentially unknown. Here, for the first time, we show the surface roughness of marine bacteria, evaluated as the root mean square deviation of height (Rq), determined by atomic force microscopy of over 1000 cells of coastal and offshore bacteria in the upper ocean. The Rq varied about 10‐fold among cells (range: 1.0–13.7 nm) and decreased with increasing seawater temperature, implying that bacteria–nanoparticle interactions differ among oceanographic areas. Microcosm experiments using two Gammaproteobacteria (isolated from coastal waters) and modeled with nanoparticle (polystyrene beads and viruses) show that the Rq is a strong predictor of nanoparticle attachment to marine bacteria, that is, bacterial nanoparticle scavenging increases with Rq. This relationship can be explained by steeper peaks/valleys and larger surface area of rougher cells. Measurement of nanoscale surface topography of marine bacteria provides novel insights into bacterial strategies for resource utilization and their contribution to marine biogeochemical cycles.